2021
DOI: 10.1063/5.0031045
|View full text |Cite
|
Sign up to set email alerts
|

Marangoni-driven instability patterns of an N-hexadecane drop triggered by assistant solvent

Abstract: Flows of thin fluid layers spreading, which have a distinguished history, have been studied since the days of Reynolds, who was among the early researchers to examine flows. Different from surfactant-driven spreading, which is currently the most common subject of study, we observe the spreading process of n-hexadecane driven by volatile silicone oil at the surface of the aqueous substrates and explore the influence of Marangoni flow caused by surface tension gradient on liquid-driven spreading. We find that on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…They found that when the concentration of aqueous IPA solution exceeded 0.35, the IPA droplets spontaneously spread and split into numerous tiny droplets. Zhao et al [5] observed n-hexadecane droplets spreading on the aqueous substrates with different surface tensions, and the results showed that there existed two instability modes, which were caused by the Marangoni effect. Woodley et al [6] investigated the dichloromethane droplets spreading on an aqueous substrate, then a unique highly ordered pattern was formed.…”
Section: Introductionmentioning
confidence: 99%
“…They found that when the concentration of aqueous IPA solution exceeded 0.35, the IPA droplets spontaneously spread and split into numerous tiny droplets. Zhao et al [5] observed n-hexadecane droplets spreading on the aqueous substrates with different surface tensions, and the results showed that there existed two instability modes, which were caused by the Marangoni effect. Woodley et al [6] investigated the dichloromethane droplets spreading on an aqueous substrate, then a unique highly ordered pattern was formed.…”
Section: Introductionmentioning
confidence: 99%